Two brownish reticulated patches on the thigh - Sofia Antunes-Duarte; Rita Bouceiro Mendes; Luís Soares- (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
A 41-year-old healthy man presented with a 2-year history of asymptomatic, progressively enlarging lesions on the external aspect of the left thigh. Its onset could not be correlated with trauma, medication or contact with any substance.